Photoinduced Crosslinking of Polymers Containing Pendant Hydroxyl Groups by Using Bisbenzodioxinones - Kumbaraci, Volkan; Talinli, Naciye; Yagci, Yusuf (Wiley, 2007)
AbstractIn the present study, it has been demonstrated that polymers containing pendant hydroxyl groups can undergo photoinduced crosslinking upon irradiation in the presence of bifunctional benzodioxinone. Irradiation of the copolymers of 2‐hydroxyethyl methacrylate (HEMA) and methyl methacrylate (MMA) in dichloromethane and THF solutions or in films containing bisbenzodioxinone, namely 5‐[9‐(4‐oxo‐2,2‐diphenyl‐4H‐benzo[d][1,3]dioxin‐5‐yloxy) nonyloxy]‐2,2‐diphenyl‐4H‐benzo[d][1,3]dioxin‐4‐one resulted in the formation of insoluble networks. Model studies using monofunctional napthodioxinone, namely 7‐hydroxy‐2,2‐diphenyl‐4H‐naphtho[2,3‐d][1,3]dioxin‐4‐one, revealed that crosslinking occurs via inter‐chain ester formation between photochemically generated keten intermediates and pendant hydroxyl groups.magnified image